The impact of family support, social support and social information towards stress cases on covid-19 survivors : a cross-sectional study - Bs Titi Haerana; M Fais Satrianegara; Hasridah Hasridah (Riset Informasi Kesehatan, 2022)
Background : Covid-19 causes enormous panic and anxiety in society. Infection-induced immune system disorders can cause psychopathology, and the remaining symptoms of psychiatry are observed after the coronavirus outbreak. Survivors of COVID-19 appear to have an increased risk of residual psychiatric symptoms, and psychiatric diagnoses that occur due to excessive worry and anxiety. Worry and anxiety themselves can cause stress. The purpose of this study was to see the influence of family support, social support, and social information on stressful events in Covid-19 survivors in the Nuha District of East Luwu Regency in 2021. Method : This research is quantitative research with an approach of Observational analytics with a Cross-sectional design with random sampling techniques, with a sample of 1781 populations Results : The results showed that for the family support variable is (p=0.004; R2 = 0.025; Y = a + bX or 1.952 + 0.743 X). Social support for stressful events in Covid-19 survivors is (p=0.000; R2 = 0.039; Y = a + bX or 1.973 + 0.556 X) and the influence of social information on stressful events in Covid-19 survivors is (p=0.000 ; R2 = 0.052; Y = a + bX or 1.667 + 0.667 X. Conclusion : There is an influence on family support, social support, social information on the occurrence of stress on Covid-19 survivors in Nuha District East Luwu in 2021.